Pharmacological interactions between adenosine A2A receptor antagonists and different neurotransmitter systems. (November 2020) - Pinna, Annalisa; Serra, Marcello; Marongiu, Jacopo; Morelli, Micaela
Abstract: While Parkinson's disease (PD) is traditionally characterized by dopaminergic neuron degeneration, several neurotransmitters and neuromodulators besides dopamine are also involved in the onset and progression of the disease and its symptoms. The other principal neurotransmitters/neuromodulators known to control basal ganglia functions and, in particular, motor functions, are GABA, glutamate, serotonin (5-HT), noradrenaline, acetylcholine, adenosine and endocannabinoids. Among these, adenosine is the most relevant, acting through its adenosine A2A receptor. Work in experimental models of PD has established the effects of A2A receptor antagonists, including the alleviation of disrupted dopamine functions and improved efficacy of dopamine replacement therapy. Moreover, positive interactions between A2A receptor antagonists and both D2 and D1 receptor agonists have been described in vitro at the receptor–receptor level or in more complex in vivo models of PD, respectively. In addition, the interactions between A2A receptor antagonists and glutamate ionotropic GluN2B -containing N -Methyl-d -aspartic acid receptors, or metabotropic glutamate (mGlu) receptors, including both mGlu5 receptor inhibitors and mGlu4 receptor activators, have been reported in both in vitro and in vivo animal models of PD, as have positive interactions between A2A and endocannabinoid CB1 receptor antagonists. At the same time, a combination of A2A receptor antagonists and 5-HT1A –5-HT1B receptor agonists have been described to modulate the expression of dyskinesia induced by chronic dopamine replacement therapy. Highlights: Adenosine A2A R interacts with several neurotransmitter/neuromodulator receptors. A2A R establishes receptor-receptor interactions or basal ganglia network interactions. A2A R antagonists plus 5-HT1A/1B R agonists affect dyskinesia. A2A R antagonists plus 5-HT1A/1B R agonists do not impair motility.